Project Based Learning dalam Pembelajaran Kaiwa di Masa Pandemi - Yuniarsih; Tia Ristiawati; Fitri Fauziyyah (SoCul: International Journal of Research in Social Cultural Issues, 2021)
The purpose of this study is to describe the implementation and results of project based learning (PjBL) in learning kaiwa II at Japanese Language Education Study Department of Faculty of Languages ​​and Arts UNJ during a pandemic to improve kaiketsu nouryoku (problem solving competency), ibunka rikai nouryouku (competence in intercultural understanding), and kadai suikou nouryoku (competence in accomplishing tasks), and also describe students’ responses regarding project based learning in this kaiwa class. This project produced drama scripts and drama videos. Based on the results of the questionnaire, it is known that drama is one of the methods favored by students. From the results of the video recording, it is known that the drama is less natural, but the required learning materials have been fulfilled in the scenario. 68.2% of students stated that it was effective to use PjBL in Kaiwa II learning, but there were also some students who did not know about this project based learning. Thus, the teacher as a facilitator must explain at the beginning of the lecture about PjBL and its usefulness in learning. Furthermore, to meet the demands of KPI in MBKM, this PjBL based drama can be used as an alternative in kaiwa learning.